2006
DOI: 10.1016/j.jaci.2006.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dog ownership and high endotoxin on wheezing and atopy during infancy

Abstract: Background-Increased exposure to microbial products early in life may protect from development of atopic disorders in childhood. Few studies have examined the relationship of endotoxin exposure and pet ownership on atopy and wheezing during infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 47 publications
5
90
2
5
Order By: Relevance
“…In this same high-risk cohort, however, exposure to high levels of endotoxin during infancy increased the risk for development of asthma and late-onset wheezing at age 7 years (45). Previously in this birth cohort we reported that exposure to both multiple dogs and high endotoxin during infancy was protective for wheeze at age 1 year (34). The effect of either exposure alone, however, was not significant.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In this same high-risk cohort, however, exposure to high levels of endotoxin during infancy increased the risk for development of asthma and late-onset wheezing at age 7 years (45). Previously in this birth cohort we reported that exposure to both multiple dogs and high endotoxin during infancy was protective for wheeze at age 1 year (34). The effect of either exposure alone, however, was not significant.…”
Section: Discussionmentioning
confidence: 53%
“…A total of 37 samples were below the lower limit of detection (6 endotoxin units/ mg of dust). Endotoxin levels below the LOD were analyzed as LOD/2 (34,35).…”
Section: Study Populationmentioning
confidence: 99%
“…Other studies of exposure to dogs have suggested that protection against wheezing may be mediated by high levels of endotoxin. 130 Gene-by-environment interactions The effects of gene-by-environment interactions in asthma are complex. In some cases the genes code for enzymes that detoxify inhaled agents (e.g., glutathione transferase genes and environmental pollution), whereas in other cases, the exposures may have a more direct effect on gene expression via epigenetic mechanisms, such as DNA methylation or histone modification.…”
Section: Allergic Sensitizationmentioning
confidence: 99%
“…Previous studies have mainly focused on cat allergen exposure and cat ownership, while not many prospective studies have specifically discussed the effect of childhood dog contact. Cohort studies have associated early childhood dog ownership with reduced risk of wheezing [1][2][3] and ALMQVIST et al [4] have reported that dog ownership in infancy seems to reduce the risk of asthma. Conversely, the Dutch Prevention and Incidence of Asthma and Mite Allergy cohort has reported that infancy dog allergen exposure has no effect on the development of wheezing or asthma [5].…”
mentioning
confidence: 99%